Ward committee challenges in South Africa’s Local Municipalities: functions and dysfunctions - Sekgala, M. P. (Journal of Public Administration and Development Alternatives (JPADA), 2016)
In accordance with the provisions of the Constitution of the Republic of South Africa (1996), local municipalities have established ward committees as a means of involving stakeholder communities in public affairs. Community participation is firmly entrenched as a pillar of local government in a democratic South Africa. Municipalities are encouraged to work with people in order that they may not seek to be passive beneficiaries; and, the Municipal Structures Act (117 of 1998) provides for the modus operandi for the creation of ward committees. As platform for public participation, ward committees are expected to facilitate communication between municipalities and communities as well as enhance participatory democracy at local level through decision-making processes. In reality, though, ward committee have faced teething challenges, especially in respect of influencing the decision-making processes. This article examines the functions and dysfunctions of ward committees precipitated by the prevalent challenges in the municipal decision-making processes. The article concludes that the challenges faced by the ward committees are associated with the existing local municipal governance.
Journal article
Keywords: Ward Committees; Ward Councillors; Municipalities; Power; Municipal Councils; Municipal government -- South Africa; Local government -- South Africa; City council members -- South Africa